2014
DOI: 10.1039/c4lc00286e
|View full text |Cite
|
Sign up to set email alerts
|

Compact microfluidic device for rapid concentration of PET tracers

Abstract: HPLC purification and reformulation of positron emission tomography (PET) tracers can lead to significant dilution of the final product, making it difficult to produce a sufficiently high radioactivity concentration for some applications (e.g. small animal imaging, in vitro assays, and labelling of proteins with prosthetic groups). This is especially true for molecules with lengthy or low-yield syntheses. Starting the synthesis with more radioactivity increases the final radioactivity concentration but increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The design is based on preliminary work we previously reported [21] but with numerous improvements. The new device (Figure 1) measures 120 mm × 120 mm in lateral dimensions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The design is based on preliminary work we previously reported [21] but with numerous improvements. The new device (Figure 1) measures 120 mm × 120 mm in lateral dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work suggested that some PET tracers had adverse reactions (adsorption or absorption) with the chip [21]. Suspecting a material-dependence, we fabricated sample layers from a variety of materials, including: poly(methyl methacrylate) (PMMA), polytetrafluoroethylene (PTFE), glass-filled PTFE (glass-PTFE), polyetherimide (Ultem), cyclic olefin copolymer (COC) and polyether ether ketone (PEEK).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations